Evaluation and Improvement of College Dance Course Based on Multiple Intelligences Theory - Bi Zhang; Yi Gang (Research and Advances in Education, 2024)
Based on the theory of multiple intelligences, this paper discusses the methods and strategies for the evaluation and improvement of college dance courses. Firstly, this paper introduces the concept and development of multiple intelligence theory and emphasizes its complement and perfection to traditional intelligence theory. Then, it analyzes the problems and shortcomings of current college dance courses, including overemphasis on skill training and single evaluation criteria. Then, it puts forward the curriculum evaluation index based on the theory of multiple intelligences, including the evaluation of students’ multiple intelligences development and the evaluation of curriculum design and teaching methods. At the same time, curriculum evaluation tools and methods are discussed, such as questionnaire survey, observation record, learning achievement display and student self-rating. In the aspect of curriculum improvement and perfection strategy, it emphasizes the application of multiple intelligence theory, interdisciplinary integration and the introduction of scientific and technological means. In terms of curriculum implementation and effect evaluation, the importance of students’ comprehensive intelligent evaluation and students’ feedback is emphasized. Finally, the paper summarizes the practical value of the evaluation and improvement of college dance courses based on the theory of multiple intelligences and looks forward to the future research direction and prospects.